1990
DOI: 10.1056/nejm199012063232306
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Costs of Diagnostic Imaging in Office Practice — A Comparison of Self-Referring and Radiologist-Referring Physicians

Abstract: Physicians who do not refer their patients to radiologists for medical imaging use imaging examinations more frequently than do physicians who refer their patients to radiologists, and the charges are usually higher when the imaging is done by the self-referring physician. From our results it is not possible to determine which group of physicians uses imaging more appropriately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
0
2

Year Published

1991
1991
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 334 publications
(98 citation statements)
references
References 13 publications
3
93
0
2
Order By: Relevance
“…The official position of the AMA is that "In general, physicians should not refer patients to a healthcare facility outside their office practice at which they do not directly provide services when they have an investment interest in the facility (Mitchell and Scott, 1992b). The AMA has also stated that the referral of patients to facilities in which physicians have an ownership interest is permissible provided that patients are apprised of this relation and have other choices, and provided that physicians always act to their patients best interests (Hillman et al, 1990).…”
Section: Influence On Self Referral: Pros and Consmentioning
confidence: 99%
See 4 more Smart Citations
“…The official position of the AMA is that "In general, physicians should not refer patients to a healthcare facility outside their office practice at which they do not directly provide services when they have an investment interest in the facility (Mitchell and Scott, 1992b). The AMA has also stated that the referral of patients to facilities in which physicians have an ownership interest is permissible provided that patients are apprised of this relation and have other choices, and provided that physicians always act to their patients best interests (Hillman et al, 1990).…”
Section: Influence On Self Referral: Pros and Consmentioning
confidence: 99%
“…The authors concluded that the differences could not be attributed to the physicians' specialty or the diagnostic classifications of the patients (Hillman et al, 1990). Hillman et al (1992) compared charges and utilization of diagnostic imaging in a broad range of clinical presentations and found that physicians who own imaging technology employ imaging significantly more often than do physicians who refer their imaging examinations to non-entity radiologists.…”
Section: Studies On Joint-ventures and Self-referralmentioning
confidence: 99%
See 3 more Smart Citations